Minimasi Jarak Perpindahan Material Menggunaan Algoritma Blocplan dalam Perancangan Tata Letak Proses Produksi Produk Vulkanisir Ban - Richardo, Victor; Santoso, Dewi Agustini; Talitha, Tita (Universitas Dian Nuswantoro, 2017)
The design of the layout aims to optimize aspects of productivity, processing time, worker fatigue, cost & distance of movement of material on the production floor. Optimizations regarding material displacement distance typically focus on minimizing the distance between the production units within the manufacturing company. This study conducted a case study on UD Utama Tires which is one of the companies manufacturing retread tire trucks located in Semarang. The company has crossmovement related problems between production units and departmental layout that is not in line with the production process flow, while the availability of production space is only 30x15 meters and there are 12 departments. The observation result shows the distance of material transfer in the heat-processing unit is 111.96 m and the cold-processing unit is 100.63. Optimization needs to be done to minimize the material distance between the units of the process. Blocplan algorithm was chosen as the method of arranging the company layout and obtained the result of 20 alternative proposed new layout to then selected one of the proposals with the highest layout score. The result of this research is the 15th proposed alternative with the highest layout-score value is 0.82, so it can be concluded that the optimum model can minimize the distance of the material production movement by 63.8m in the heat-processing unit with the effectiveness rate 43.02% and 69.1m in the process unit cold with effectiveness rate 31,33%